CONTRIBUCION A LOS ESTUDIOS EN ANELIDOS GLOSSOSCOLECIDOS DE COLOMBIA. MORFOLOGIA Y ANATOMIA DE Martiodrilus crassus - Iafrancesco V., Giovanni M.; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá. Museo de Ciencias Naturales, Universidad de la Salle. (2013)
The present work is a contribution to the morphologic and anatomic studies of. the lombriz capitana e earth worm) Martiodrilus crassus (Annelid: Glossoscolecidae)from the NaturalNationaiPark, Cueva de los Guácharos, Department of Huila, collected in La Mensura andEl Pesebre at 2.850 m.s.n.m. Described within are climatic characteristics of the habitat related to the annelid, materials and methods employed for its capture, collectiort; conditioning, dissection and preservation of the samples. Also, its morphologic and anatomic description refering to matemeric, bodywall, legs e quetas ), pores, pillicle, clypeus and muscular ' layers involved in its externa! morphology. And in addition, information about the digestive, circulatory, nervous, éxcretory and reproductive systems, which are part of its interna! anatomy.